2014
DOI: 10.1109/jdt.2013.2277590
|View full text |Cite
|
Sign up to set email alerts
|

Flexible TFT Circuit Analyzer Considering Process Variation, Aging, and Bending Effects

Abstract: This paper presents a SPICE-based simulator, FlexiAnalyzer, for flexible thin-film transistor (TFT) circuits. This simulator performs four types of analysis: yield analysis, aging analysis, performance analysis, and weak spot analysis. This simulator considers three important effects: 1) threshold voltage variation of manufacturing process; 2) threshold voltage shift due to aging effect; and 3) mobility change due to bending effect. Six different OLED pixel drivers designed in 8-m amorphous silicon TFT technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…One step in this direction was done by Ma et al, 217 who included strain-induced l FE variations into a HSpice-based flexible circuit analyzer. Furthermore, purely mechanical simulations of flexible n-type vacuum-processed metal oxide semiconductor TFTs have also been reported.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One step in this direction was done by Ma et al, 217 who included strain-induced l FE variations into a HSpice-based flexible circuit analyzer. Furthermore, purely mechanical simulations of flexible n-type vacuum-processed metal oxide semiconductor TFTs have also been reported.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…To date, only Ma et al have shown a HSpice-based simulator, which is able to include the threshold voltage variations induced by mechanical strain, as well as by process modifications and aging. 217 b. Digital circuits.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…In particular, flexible electronics are usually associated with large variations on V th and µ. According to previous work in [22], the relative standard deviation (std) of V th and µ are modeled as ±20% and ±15% respectively, while the relative std of device physical sizes (W and L) are modeled as ±3%. The aging effect is calculated according to the model proposed in [20].…”
Section: A Experiments Setupmentioning
confidence: 99%
“…YieldAnalyzer is a SPICE-based simulator that performs many Monte Carlo trials considering aging, bending and process variation [21], [22]. The distribution of process variation in threshold voltage can be modeled as inter-die and intra-die variations.…”
Section: A Yieldanalyzermentioning
confidence: 99%